Towards inclusive conservation governance in forest landscape co-management: Insights from the Yarlung Tsangpo river basin - Ting Ma; Peng Wang; Ding Yang; Zhi Wang (Trees, Forests and People)
Co-management involves sharing resource management duties between the state and user groups. In the Yarlung Tsangpo River Basin (YTRB), resource management is fragmented across township-level governments, resulting in coordination challenges and the exclusion of critical stakeholders from decision-making processes. This research presents feedback and recommendations from focus group discussions with local residents and officials in the YTRB on their experiences with ''forest landscape co-management.'' Participants advocated for a fairer and more inclusive conservation mechanism. The paper concludes with discussions on key issues such as equity, empowerment, and gender, emphasizing the need for a shift from co-management to an inclusive conservation governance model. This model would facilitate joint deliberations and decision-making among diverse stakeholders. The study underscores that adopting an inclusive conservation governance approach in the YTRB can enhance forest resource protection and conservation through shared responsibility. It also suggests that such a framework can organize forest resource management to achieve local sustainability. Furthermore, the research provides a baseline for forest resource planners to adopt shared responsibility, mitigating conflicts among users and ensuring that those affected by decisions can understand and accept common resource management goals.